"Siempre Adistanciados" : Ideology, Equity, and Access in Peruvian Emergency Distance Education for Spanish as a Second Language. Issue Volume 39(2022)Special Issue (31st December 2022) - Back, Michele; Zavala, Virginia; Franco, Raiza
Abstract : Although the COVID-19 pandemic has profoundly affected K–12 education worldwide, Peru has faced particularly unique challenges. A combination of quarantine requirements and unequal access to remote learning technology led to the creation of a series of multimodal programs by Peru's Ministry of Education under the umbrella title Aprendo en Casa [I Learn at Home]. Modules for preschool, primary, and secondary grades are broadcast via national television and radio networks, as well as posted on YouTube in an attempt to reach as many learners in the country as possible. In this article, we focus on Aprendo en Casa's radio broadcasts for Spanish as a second language (SL2). Our data comprise transcribed SL2 radio broadcasts, educational materials, and interviews with primary school teachers. Findings indicate that a lack of access to technology in rural areas, even for radio broadcasts, is inscribed in historical inequities and ideologies regarding the rural population, exacerbating the so-called "digital divide" and complicating the traditionally dichotomous perspective on this divide. We highlight student and parent difficulties with access and technological know-how, as well as some of the creative ways that teachers provided access to the curriculum for students and family members, often at risk to their own health and finances. We conclude with suggestions for improving research and practice in emergency distance language education for marginalized populations.